Training science centre Explainers. The Techniquest experience - Colin Johnson (JCOM: Journal of Science Communication, 2005)
Techniquest was established in 1986, and in 1995 moved to its current premises at Cardiff Bay, South Wales. This was the first purpose-built science centre in the UK. It receives around 200,000 visitors every year to its exhibition, and to its programmes for schools and public audiences in the theatre, laboratory, discovery room and planetarium. The author joined the Techniquest project in 1985, became a staff member in 1990 and was the Chief Executive from 1997 until his retirement in 2004. Techniquest has three “out-stations” in Wales, and is responsible for the supply and maintenance of exhibits to the Look Out Discovery Centre in Bracknell, England. There is a Techniquest gallery at the Lisbon Pavilhão do Conhecimento - Ciência Viva, and a traveling exhibition, SciQuest, in South Africa which was also supplied by Techniquest. All these centres rely on the effective intervention of “Explainers” (at Techniquest we call them “Helpers”) to provide the best possible experience for visitors. At its most demanding, the tasks of an Explainer are varied and intensive, yet there may be times when the duties are mundane or even dull. When you rely on people to act as both hosts and housekeepers, to provide both support and stimulus, and to be both welcoming and watchful, you are asking a great deal. This article raises some of the issues concerned with the recruitment and retention of Explainers, their training and management, and the way in which their role is recognized and valued by the science centre as a whole.